2005
DOI: 10.1506/75ce-hat9-rh17-lad7
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Legal and Financial Reporting Environments and Forecast Performance of Individual Analysts*

Abstract: We test the ability of analyst characteristics to explain relative forecast accuracy across legal origins (common law versus civil law). Common‐law countries generally have more effective corporate governance mechanisms, including stronger investor protection laws and inputs provided through higher‐quality financial reporting systems. In this type of environment, we predict that analysts with superior ability and resources in common‐law countries will more consistently outperform their peers because appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
96
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 48 publications
14
96
0
1
Order By: Relevance
“…For example, Barniv et al [5], Basu et al [32], Ashbaugh et al [6], and Hope [7,8] offer evidence that the accuracy of analysts' earnings forecasts varies around the world and that such variation relates positively to disclosure practices and investor protection. Barniv et al [5] found that analysts in commonlaw countries outperform their peers in civil-law countries and therefore suggest an association between legal and financial reporting environments and analysts´ forecast behaviour. Analysts may also have greater incentives to forecast accurately in well-developed capital markets (strong shareholder protection countries), where investors may exhibit greater demand for earnings forecasts [5].…”
Section: Hypothesismentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Barniv et al [5], Basu et al [32], Ashbaugh et al [6], and Hope [7,8] offer evidence that the accuracy of analysts' earnings forecasts varies around the world and that such variation relates positively to disclosure practices and investor protection. Barniv et al [5] found that analysts in commonlaw countries outperform their peers in civil-law countries and therefore suggest an association between legal and financial reporting environments and analysts´ forecast behaviour. Analysts may also have greater incentives to forecast accurately in well-developed capital markets (strong shareholder protection countries), where investors may exhibit greater demand for earnings forecasts [5].…”
Section: Hypothesismentioning
confidence: 99%
“…Barniv et al [5] found that analysts in commonlaw countries outperform their peers in civil-law countries and therefore suggest an association between legal and financial reporting environments and analysts´ forecast behaviour. Analysts may also have greater incentives to forecast accurately in well-developed capital markets (strong shareholder protection countries), where investors may exhibit greater demand for earnings forecasts [5]. Chang et al [4] studied the extent and accuracy of analysts' activity across 47 countries around the world and found forecast accuracy to be lower in civil-law countries than in common-law countries.…”
Section: Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…This allows us to control effectively for differences in institutional factors, like regulatory requirements or the enforcement system. Such factors have been shown to vary across countries and to be important determinants of analysts' forecast quality (Hope 2003a;Hope 2003b;Hope 2004;Barniv, Myring, and Thomas 2005 (2007) provide evidence for the high degree of differences between IAS/IFRS and German GAAP.…”
Section: Restriction To Germanymentioning
confidence: 99%